2015
DOI: 10.3892/ijo.2015.3161
|View full text |Cite
|
Sign up to set email alerts
|

miR-506 regulates breast cancer cell metastasis by targeting IQGAP1

Abstract: MicroRNA (miRNA or miR)-506 is a novel miRNA related to the survival of breast cancer patients. However, the mechanism underlying miRNA-506 involvement in breast carcinogenesis remains unclear. In the present study, we found that miR-506 was downregulated in human breast malignant tissues and breast cancer cell lines by RT-qPCR analysis, and the expression level of miR-506 was decreased with the increasing of tumor stage. Subsequently, gain-of-function and loss-of-function experiments were performed in vitro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…On the other hand, it has been shown that the downregulation of hsa-miR-513c promotes the proliferation and invasiveness of neuroblastoma and glioma cells [38,39]. Similar to that downregulation of hsa-miR-506, leads to increased proliferation, invasiveness, and epithelial to mesenchymal transition in breast gastric and ovarian cancer [40][41][42]. Moreover, in vitro studies showed that overexpression of this miRNA is responsible for the increased sensitivity of colorectal cancer cells to chemotherapy [42].…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, it has been shown that the downregulation of hsa-miR-513c promotes the proliferation and invasiveness of neuroblastoma and glioma cells [38,39]. Similar to that downregulation of hsa-miR-506, leads to increased proliferation, invasiveness, and epithelial to mesenchymal transition in breast gastric and ovarian cancer [40][41][42]. Moreover, in vitro studies showed that overexpression of this miRNA is responsible for the increased sensitivity of colorectal cancer cells to chemotherapy [42].…”
Section: Discussionmentioning
confidence: 86%
“…21,22 Furthermore, miR-506 inhibits cell proliferation, adhesion, and invasion in breast cancer cells by inactivating IQGAP1 and its downstream ERK/MAPK signaling pathways. 23 Ectopic expression of miR-506 suppressed epithelial-to-mesenchymal transition and angiogenesis in gastric cancer. 24 Depletion of miR-506 promoted apoptosis in retinoblastoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of miR-506 inhibited the proliferation, metastasis, and EMT of breast cancer cells (35,36). Furthermore, miR-506 suppressed the metastasis of breast cancer cells by targeting the IQ motif containing GTPase-activating protein 1 (29). In gastric cancer, miR-506 inhibited EMT by targeting ETS1 (37) or SNAI2 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic research revealed that FOXQ1 has a putative binding site for miR-506 (Fig. 4A), a well-recognized tumor-suppressor miRNA (28,29). A dual-luciferase reporter assay was performed to verify whether or not FOXQ1 is a target gene of miR-506.…”
Section: Foxq1 Is a Potential Target Of Mir-506mentioning
confidence: 99%